Morphology and Mineral Analysis of Coal in Senoni Village, Sebulu District, Kutai Kartanegara Regency Using SEM-EDS - Jamilah, Nur (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2025)
Coal is formed through the process of coalification, which occurs with increasing temperature, pressure and time. The coalification process produces coal of varying quality depending on the level of organic maturity. Coal quality parameters are influenced by the minerals contained in the coal. To identify minerals in coal, a scientific approach can be used, namely SEM-EDS (Scanning Electron Microscope-Energy Dispersive Spectroscopy). In Senoni Village, coal mining is still minimal. To find out whether the coal in the area has good quality and has prospects for mining, it is necessary to do a coal quality test, namely by looking at the minerals contained in the coal. The first research stage is to take coal samples in the research area. Then the sample is prepared, namely making the sample in the form of chunks into granules with a size of 40 mesh. Furthermore, the SEM-EDS characterization test was carried out to determine the morphology and elemental content found in coal. The results obtained show that the minerals contained in coal are quartz, marcasite and calcite minerals. As well as the percentage of elemental content (C) 83.3%, (O) 16.0%, Na 0.1%, Al 0.2%, Si 0.1%, S 0.2% and Ca 0.1%. Based on the carbon content, this coal is classified as batuminous (good quality).